The Effectiveness of Mobile Collaborative Learning on Students’ Writing Performance by Implementing Magnet Summary Strategy - Masyhud, Ahsanul; Maruf, Nirwanto; Asari, Slamet (JET ADI BUANA, 2023)
The purpose of the study was to examine the effectiveness of using Mobile Collaborative Learning (MCL) and Magnet Summary Strategy (MSS) on students’ writing performance and their perceptions towards these strategies. This study utilized a pre-test and post-test control group quasi-experimental design. The results of the paired sample t-test revealed a statistically significant difference between the average pre-test score of 45.8000, indicating a lower level of knowledge among participants before the intervention, and the average post-test score of 68.2800, indicating a substantial improvement in knowledge following the interventions. The intervention used MCL and MSS to help students summarize and organize information, which resulted in improved writing performance. moreover, the significance level of 2-tailed test was less than 5% demonstrating that the difference in the pre-test and post-test scores was statistically meaningful. Thus, it is improbable that the variance in scores happened merely by chance, indicating that the intervention had considerable impact on the participants’ knowledge. The results also showed that the implementation of MCL and MSS helped students to improve their social skills. They appreciated the opportunity to collaborate and communicate with their peers, which helped them to develop their interpersonal skills and learn from each other. Moreover, the implementation of MCL and MSS resulted in a sense of group success when working on group activities, which contributed to a positive learning experience. Overall, the study suggests that using MCL and MSS can be an effective approach to improve students’ writing performance and their social skills.